2020
DOI: 10.3390/molecules25030759
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing the Oil-in-Water Emulsions Using the Mixtures of Dendrobium Officinale Polysaccharides and Gum Arabic or Propylene Glycol Alginate

Abstract: Coconut oil-in-water emulsions were prepared using three polysaccharides: Dendrobium officinale polysaccharide (DOP), propylene glycol alginate (PGA), gum arabic (GA) and their polysaccharide complexes as emulsifiers. The effects of the ratio of the compounded polysaccharides on their apparent viscosity and interfacial activity were explored in this study. The average particle size, zeta potential, microstructure, rheological properties, and physical stability of the emulsions prepared with different compound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…The OPEO‐LSSG/LPSG emulsion had the smallest particle size (479.2 nm), while OPEO‐LSSG emulsion had the largest particle size (673.3 nm). This result agreed with those found by Wang, Tian, and Xiang (2020), who reported that emulsions prepared with compound polysaccharides exhibited smaller average particle sizes than polysaccharides individually.…”
Section: Resultssupporting
confidence: 93%
“…The OPEO‐LSSG/LPSG emulsion had the smallest particle size (479.2 nm), while OPEO‐LSSG emulsion had the largest particle size (673.3 nm). This result agreed with those found by Wang, Tian, and Xiang (2020), who reported that emulsions prepared with compound polysaccharides exhibited smaller average particle sizes than polysaccharides individually.…”
Section: Resultssupporting
confidence: 93%
“…The effects of five different incubation temperatures (25,30,35,40 and 45 • C) on MOE6-EPS production were tested at pH 7 with 180 rpm shaking for 7 days of incubation. This was followed by evaluating the effect of different incubation periods and were studied over an incubation time of 10 days at 180 rpm, 35 • C, and an initial pH of 7.…”
Section: Optimization For the Production Of Moe6-epsmentioning
confidence: 99%
“…Research efforts have been directed to the development of natural sources for emulsifiers and surfactants with higher degradability, lower toxicity and reasonable affordability [23]. Polysaccharides have been shown to form emulsions in addition to stabilizing mixtures [25,26]. A natural emulsifier of industrial importance is xanthan gum, which is produced from Xanthomonas campestris and is used in many pharmaceuticals such as creams and suspensions [27].…”
Section: Introductionmentioning
confidence: 99%
“…This inding showed that the gelatin in combination with span could be used as emulsi iers to provide better electrostatic repulsion between emulsion droplets. (Wang et al, 2020).…”
Section: Zeta Potentialmentioning
confidence: 99%